Lymphoid-rich lesions of the salivary glands: how not to miss malignancy - Krishna, K. Hari; S., Supreetha M.; Suresh, T. N. (International Journal of Research in Medical Sciences, 2026)
Salivary gland lesions with prominent lymphoid components pose a significant diagnostic challenge in cytopathology due to considerable morphological overlap among reactive, benign, and malignant conditions. While fine-needle aspiration cytology (FNAC) is commonly used as a first-line diagnostic tool, its accuracy may be limited by sampling variability and tumor heterogeneity, particularly in lymphoid-rich neoplasms where the epithelial component is minimal or obscured. This report presents three cases that illustrate frequent diagnostic pitfalls in lymphoid-rich salivary gland lesions: acinic cell carcinoma with prominent lymphoid stroma initially misdiagnosed as chronic sialadenitis, adenoid cystic carcinoma of the submandibular gland with cervical lymph node metastasis, and Warthin’s tumor mimicking chronic granulomatous sialadenitis on cytology. These cases underscore the importance of meticulous cytomorphological assessment, adequate sampling, and comprehensive clinicoradiological correlation. Histopathological examination remains indispensable for establishing a definitive diagnosis in ambiguous cases. Greater awareness of lymphoid-rich variants of salivary gland tumors and maintaining a low threshold for surgical biopsy are essential to avoid missed or delayed diagnoses of malignancy.